Osteoporosis in an Adolescent Female: A Case Report (Bangladesh Journal of Nuclear Medicine, 2024)
Osteoporosis constitutes a significant disease burden globally. While this disease has been historically associated with postmenopausal women and elderly men, osteoporosis in younger adults does occur in the setting of chronic disease, medications that affect bone metabolism, and other risk factors. Among those, glucocorticoids are an important risk factor for bone fragility in children or young adults with serious illnesses, largely due to their direct adverse effects on skeletal metabolism. In this report, we present a case of a 16-year-old female diagnosed with glucocorticoid-induced osteoporosis (GIO). She had been on prednisolone for more than a year owing to progressive glomerulonephritis with a nephrotic picture. She developed severe low back pain and restricted mobility and sought urgent care. Spine radiographs showed osteoporotic changes, which warranted further investigations including bone mineral densitometry (BMD) by dual energy x-ray absorptiometry (DXA). BMD revealed a T-score and Z-score of -3.1 at lumbar spine, suggestive of osteoporosis. In light of her medical history and the BMD findings along with a low basal cortisol level, a diagnosis of glucocorticoid-induced osteoporosis (GIO) was made. She was commenced on Teriparatide, a recombinant human parathyroid hormone analog and subsequently discharged upon regaining ambulation.Bangladesh J. Nuclear Med. 26(2): 210-214, 2023